A Theory of City Biogeography and the Origin of Urban Species - Dunn, Robert R.; Burger, Joseph Robert; Carlen, Elizabeth J.; Koltz, Amanda M.; Light, Jessica E.; Martin, Ryan A.; Munshi-South, Jason; Nichols, Lauren M.; Vargo, Edward L.; Yitbarek, Senay; Zhao, Yuhao; Cibrián-Jaramillo, Angélica (Frontiers in Conservation Science, 2022)
Many of the choices humans make with regard to infrastructure, urban planning and other phenomena have impacts that will last thousands of years. This can readily be seen in modern cities in which contemporary streets run along street grids that were laid out thousands of years prior or even in which ancient viaducts still play a role. However, rarely do evolutionary biologists explicitly consider the future of life likely to be associated with the decisions we are making today. Here, we consider the evolutionary future of species in cities with a focus on the origin of lineages and species. We do so by adjusting evolutionary predictions from the theory of island biogeography so as to correspond to the unique features of cities as islands. Specifically, the species endemic to cities tend to be associated with the grey habitats in cities. Those habitats tend to be dominated by human bodies, pet bodies and stored food. It is among such species where the origin of new lineages is most likely, although most research on evolution in cities has focused on green habitats. We conclude by considering a range of scenarios for the far future and their implications for the origin of lineages and species.